The Tumor-Immune Microenvironment and Response to Radiation Therapy - Shiao, Stephen L. (Springer US, 2010)
Chemotherapy and radiation therapy (RT) are standard therapeutic modalities for patients with cancer, including breast cancer. Historic studies examining tissue and cellular responses to RT have predominantly focused on damage caused to proliferating malignant cells leading to their death. However, there is increasing evidence that RT also leads to significant alterations in the tumor microenvironment, particularly with respect to effects on immune cells infiltrating tumors. This review focuses on tumor-associated immune cell responses following RT and discusses how immune responses may be modified to enhance durability and efficacy of RT.